Strategy Analysis In Increasing Competitiveness Taruna Nusantara High School, Magelang - Radhita Anggoro Setiawan; Bachtar Bakrie; Tina Rosa (Journal of Entrepreneur and Business, 2024)
The idea of ​​making TN High School was sparked by the Minister of Defense and Security General LB Moerdani on May 20, 1985 at the Great Pavilion of Taman Siswa Yogyakarta. He has a vision to build a school that educates the best people from all over Indonesia and produces graduates who can continue the aspirations of the Proclamator. This idea was continued by signing an MoU between the TNI and Taman Siswa, which was the first educational organization in Indonesia, the TNI through the Pang Perjuangan Foundation The purpose of this study is to determine the factors To determine the factors that influence the competitiveness of both external factors and internal factors and find out the right strategy to increase competitiveness based on the SWOT analysis approach and AHP data processing tools. Data collection techniques were obtained by interview, observation and documentation. The results of this study are based on those conducted by expert respondents on the factors that influence in increasing competitiveness in the Taruna Archipelago High School in Magelang. External Factors (Competitions from similar schools, students who fail selection at TN High School Gaining the trust of parents of students and the wider community for the next career path, the existence of student sanctions). The right strategy and is used based on Swot and AHP from the results of interviews with the expert team is to choose the strategy of Strength and Opportunity in terms of the application of quality and service in educational institutions (both in terms of Sarpras and HR). Key words: Strategy Analysis, SWOT, AHP,